Forequarter amputation for recurrent breast cancer. (2015) - Pundi, Krishna N.; AlJamal, Yazan N.; Ruparel, Raaj K.; Farley, David R.
Highlights: Forequarter amputation is an aggressive treatment for recurrent breast cancer. Some patients with regional metastatic disease do benefit from forequarter amputation. Patients with unrelenting cancer pain do gain relief from forequarter amputation. Abstract: Introduction: Localized excision combined with radiation and chemotherapy represents the current standard of care for recurrent breast cancer. However, in certain conditions a forequarter amputation may be employed for these patients. Presentation of case: We present a patient with recurrent breast cancer who had a complicated treatment history including multiple courses of chemotherapy, radiation, and local surgical excision. With diminishing treatment options, she opted for a forequarter amputation in an attempt to limit the spread of cancer. Discussion: In our patient the forequarter amputation was utilized as a last resort to slow disease progression after she had failed multiple rounds of chemotherapy and received maximal radiation. Unfortunately, while she had symptomatic relief in the short-term, she had cutaneous recurrence of metastatic adenocarcinoma within 2 months of the procedure. In comparing this case with other reported forequarter amputations, patients with non-metastatic disease showed a mean survival of approximately two years. Furthermore, among patients who had significant pain prior to surgery, all patients reported pain relief, indicating a significant palliative benefit. This seems to indicate that our patient's unfortunate outcome was anomalous compared to that of most patients undergoing forequarter amputation for recurrent breast cancer. Conclusion: Forequarter amputation can be judiciously used for patients with recurrent or metastatic breast cancer. Patients with recurrent disease without evidence of distant metastases may be considered for curative amputation, while others may receive palliative benefit; disappointingly our patient achieved neither of these outcomes. In the long term, these patients may still have significant psychological problems.